Moral harassment and mental health in medical residents: a longitudinal study - Ana Bresser Tokeshi; Renato Antunes dos Santos; Luiz Antonio Nogueira-Martins; Maria do Patrocinio Tenório Nunes; Thiago Marques Fidalgo (Brazilian Journal of Psychiatry)
Objective: This study investigated whether moral harassment contributes to anxiety, depression, and burnout among medical residents. Methods: This three-stage longitudinal study involved 218 1st-year residents, of whom 76 (34.9%) participated in all stages. The questionnaire covered demographics, mental health (using the Patient Health Questionnaire-4), burnout (using the Maslach Burnout Inventory Human Services Survey), and harassment experiences. Mental health outcomes and harassment were analyzed using logistic regression. Results: Anxiety and depression scores varied significantly, including a notable decrease in the personal accomplishment dimension of burnout. The prevalence of harassment was above 90%, and most victims were disturbed by the harassment they suffered. While a direct correlation between harassment victimization and reduced mental health was not found, seeking help exacerbated suffering, and depression and emotional exhaustion increased less among surgical residents. Conclusion: To the extent of our knowledge, this is the first longitudinal study on mental health and harassment among medical residents. The mental suffering experienced after taking action against harassment suggests that safe environments for addressing these issues are lacking in medical residencies. Further studies concerning surgical residents could shed light on their lower levels of suffering. Institutional changes are needed to support victims and create a healthy environment.